Performance of Mechanical Energy Harvesting Unit for Generating Electricity for Portal Gate System - Joni Dewanto; Oegik Soegihardjo (Journal of ICT, Design, Engineering and Technological Science, 2020)
The portal gate systems for the parking area need electricity for opening/closing the portal (barrier crossbar) and printing the parking ticket. The Mechanical Energy Harvesting Unit (MEHU) presented in this paper is designed for supplying electrical energy needed by the portal gate system for its operation. The MEHU converted the linear movement of the slider into the rotating movement of the flywheel using rack and pinion. The energy stored in the flywheel is used to turn a small electric generator attached to the energy harvesting unit that provided electricity for the portal gate system. This energy harvesting unit is designed as a breakthrough to produce electrical energy by utilizing the vehicle's weight that enters the parking space. The linear movement of the slider is gained from the weight of the vehicle that passed on the MEHU. This system is appropriate for stand-alone portal gate systems. Three categories of passenger cars (small, medium and large), each with the mass of 1300 kg, 1700 kg, and 2000 kg, respectively, were used in the experiment. The three vehicles used for these experiments were able to produce a maximum rotation of the harvesting unit's electric generator for 2500 rpm, 2890 rpm, and 3140 rpm, respectively. The testing of the harvesting unit's electric generator was done with a continuous rotation. The electrical loads were taken from LED lights with the voltage of 24 Volt, 18 Volt, and 12 Volt produces power of 19 Volt x 3.6 mAmp (4000 rpm), 17 Volt x 4.3 mAmp (3500 rpm), and 12 Volt x 11 mAmp (2400 rpm) respectively. Initial testing of the MEHU shows that this equipment is capable of producing the required electrical energy. The energy stored in the flywheel is used to turn a small electric generator attached to the energy harvesting unit that provided electricity for the portal gate system. This energy harvesting unit is designed as a breakthrough to produce electrical energy by utilizing the vehicle's weight that enters the parking space.